2021
DOI: 10.1111/idh.12565
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dental caries management using ‘CAMBRA‐kids’ mobile application for children under 5 years old

Abstract: Recently, there is an ever-increasing interest in the use of applications for smart devices and wearable devices for mobile healthcare. 1 According to the World Health Organization (WHO), the concept of m-health (mobile health) is defined by as 'medical and public health practice supported by mobile devices, such as mobile phones, patient monitoring devices, personal digital assistances (PDA) and informational & communication technology (ICT). 2 Mobile healthcare utilizes the advantage of mobility of mobile de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Healthy behaviors during childhood are the foundation of good oral health habits throughout life. A study showed that children under 5 years old had adequate cognitive ability to be managed dental caries by using a mobile application ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthy behaviors during childhood are the foundation of good oral health habits throughout life. A study showed that children under 5 years old had adequate cognitive ability to be managed dental caries by using a mobile application ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Abanto et al ( 15 ) observed a caries prevention program for children based on caries risk assessment for 2 years, and the results showed that this program could effectively prevent early caries and control active caries in children. Yeo and Lee ( 16 ) conducted caries management using mobile application for preschoolers, and it had effects on dental plaque, mineral loss and cariogenic bacteria, especially for children in the extreme high- risk group and the high- risk group.…”
Section: Introductionmentioning
confidence: 99%
“…These approaches can reach students where they are, providing them with tailored guidance on oral health behaviors, thus enhancing their overall oral health outcomes (Gayatri, 2023). Moreover, the use of mobile applications for self-examination of oral health problems can empower individuals to take charge of their oral health, promoting early intervention and prevention (Yeo & Lee, 2021). To tackle socio-economic disparities in oral health outcomes and care access, various strategies can be implemented.…”
Section: Challenges In Oral Health Education and Preventionmentioning
confidence: 99%